New technology perspectives for the autonomous and teleoperated vehicles: the experience of Antartica robots and the expected spin-off - Bonanno, G.; Fichera, A.; Moriconi, C.; Dell'Erba, Ramiro; Papalia, B.; SAGRATELLA, G. (HAL CCSD, 2003)
International audience